Don’t Get Boxed In By Your Thought Process - Davis, Lessie (Wildlife Rehabilitation Bulletin, 2005)
Have you ever scanned the Table of Contents of a new Wildlife Rehabilitation Bulletin and thought to yourself, “Nope, nothing on my species, so nothing in here for me!”? If so, you may be missing useful information that does relate to your rehabilitation work. Helpful hints or new ideas can often be found even within papers that appear, at first glance, to be utterly unrelated to your topic of interest. Rehabilitators working with different species still have many more similarities than differences, and relevant information can turn up in the most unexpected places. Think twice before discounting information simply because of the packaging. Creative readers, like scavengers for good ideas, can sniff out and take home what is helpful to them, to modify for their own purposes. Reading this way simply requires some imagination and the ability to ‘read outside the box.’ Follow me, as we take a short journey through this issue of the Bulletin to seek out tips that would be useful for a rehabilitator of almost any species.